Penguatan Geowisata Melalui Digitalisasi Informasi Geoheritage Wonocolo Berbasis GIS Dan QR Code - Oktavianus Cahya Anggara; Wendy Vio Lugianto; Aria Krisna Putra; Bagus Dwi Prasetyo; Aditya Pratama (Universitas Muhammadiyah Gorontalo, 2025)
The Teksas Wonocolo Geoheritage Area in Bojonegoro Regency holds significant educational value and represents the historical practice of traditional oil mining. However, its tourism potential remains underutilized, as indicated by low visitation rates, approximately 120 visitors per month and limited access to destination information, which is still distributed through printed brochures and an inactive official website. This study develops a digital tourism information system using Desktop Geographic Information System (GIS) integrated with Quick Response (QR) Code technology. Spatial datasets consist of administrative boundaries, road networks, rivers, and satellite imagery, while non-spatial data were obtained from field surveys, including GPS coordinates, photo documentation, and descriptive information on tourist points. These datasets were integrated into an interactive digital map that presents geographic positions, photographs, and destination descriptions. Information is accessible through QR Codes installed at strategic locations within the geoheritage area. The resulting system improves information availability, supports user navigation, and strengthens the presentation of local identity. The GIS–QR Code integration model demonstrates its potential for replication in other areas with similar characteristics as part of digital transformation efforts in the tourism sector.